2021
DOI: 10.1001/jamacardio.2020.4511
|View full text |Cite
|
Sign up to set email alerts
|

Association of SGLT2 Inhibitors With Cardiovascular and Kidney Outcomes in Patients With Type 2 Diabetes

Abstract: IMPORTANCE Sodium-glucosecotransporter2(SGLT2)inhibitorsfavorablyaffectcardiovascular(CV) and kidney outcomes; however, the consistency of outcomes across the class remains uncertain. OBJECTIVE To perform meta-analyses that assess the CV and kidney outcomes of all 4 available SGLT2 inhibitors in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

34
665
5
30

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 825 publications
(734 citation statements)
references
References 46 publications
34
665
5
30
Order By: Relevance
“…Ertugliflozin reduced risk for first HHF, for total HHF, and for total HHF/CV death events in patients with T2DM in the VERTIS CV trial, findings consistent with those reported for other members of the SGLT2 inhibitor class, 10 13 , 23 and provide additional supportive evidence for the use of SGLT2 inhibition in patients with T2DM to prevent HF-related outcomes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Ertugliflozin reduced risk for first HHF, for total HHF, and for total HHF/CV death events in patients with T2DM in the VERTIS CV trial, findings consistent with those reported for other members of the SGLT2 inhibitor class, 10 13 , 23 and provide additional supportive evidence for the use of SGLT2 inhibition in patients with T2DM to prevent HF-related outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…To date, although CV outcome trials with SGLT2 inhibitors in patients with T2DM have shown heterogeneous results with regard to the effects on CV death (HRs ranging from 0.62 to 0.98), there has been remarkable consistency in the observed reduction in risk for first event of HHF across these trials, with HRs ranging from 0.61 to 0.73. 23 In VERTIS CV, the magnitude and timing of the reduction in risk of HHF, with consistent demonstration of an early benefit after study drug initiation, and the consistency of effect between doses correspond to what has been reported for other members of the SGLT2 inhibitor class in patients with T2DM and different levels of CV risk (with and without ASCVD). 10 , 12 , 13 Similar findings have been reported in trial populations with albuminuric diabetic kidney disease, 11 and with HF and reduced EF with or without T2DM.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Their use in the highest risk class does not appear completely justified when compared with the underutilization of some pharmacological classes with proven cardiovascular benefit (i.e. GLP1-RA and SGLT2-i) [ 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A patient or a provider may value one death/HHF event averted, to be almost five times (since [24.7-19.3 Several meta-analyses about the effects of SGLT2i were published in late 2019 and early 2020 19,[22][23][24][25][26][27] with different focus (e.g., cardiovascular or renal outcomes or safety) and different search strategies than our own. The strengths of the present meta-analysis are the simultaneous consideration of a broad range of both efficacy AND safety outcomes, the inclusion of four large studies and our focus on an expanded population of patients of extremely high cardiorenal risk.…”
Section: Discussionmentioning
confidence: 99%